Influence of fly ash, cement and ground river sand on compressive strength and chloride penetration of mortar. (2020) - Saloni; Singh, Abhishek; Jatin; Kumar, Jatin; Parveen
Abstract: The study deals with the strength and chloride resistance properties of mortar prepared by combining the Portland cement 43 grade, fly-ash and ground river sand. Fly ash and ground river sand were utilized to partially replace ordinary Portland cement type I. The replacement percentage of fly ash and ground river sand was varied from 0 to 40% and the mortar mixes were prepared. Fly ash and ground river sand was processed using ball mill and sieve with openings of 45 µm (sieve No. 325) was used to obtain 3% weight retained. The mortar samples were tested for their strength (compressive), penetration (Rapid chloride) and microstructural properties. The results indicated that the strength (compressive) increased and resistance to chloride penetration was excellent. According to SEM analysis, homogeneous and dense structure of the newly developed mortar was observed. Ground river sand addition, however, reduced strength and improved chloride resistance which indicated that it made changes to only packing structure. Strength and penetration resistance were enhanced and it was due to the pozzolanic effect of fine fly ash.